Effectiveness of Administrating a Food- Supplement on Improving the Physical Performance and Immunological Profile of Swimmers - Sakoury, Mona Mostafa; Mostafa, Sally Ali; Elmaghraby, Ahmed Mohammed (International Journal of Psychosocial Rehabilitation, 2018)
The current research aims to identify the effects of administering food supplement (W3) and the effects of physical effort after administering food supplement (W3) on all physical performance and immunity variables in swimmers. The researchers used the experimental (one-group) approach with pre- and post-measurements. The researchers purposefully chose (10) swimmers (15-21 years) from Smouha Sports Club who were all registered in the Egyptian Federation of Swimming with training experience of at least (2) years. Table (1) shows characteristics of participants. The researchers measured the following variables (HR – VO2 max – WBCs – Immunoglobulins – Hematocrit – Ca) before and after effort without having (W3) and before and after effort with having (W3) as food supplement. Results indicated that:• There are statistically significant differences on all physical performance variables (HR, VO2 max, Hematocrit and Ca) after effort with administering (W3). This improved the physical performance level of swimmers.• There are statistically significant differences on all immunological variables (WBCS – IgG – IgM - IgA) after effort with administering (W3). This improved the physical performance level of